2018
DOI: 10.3389/fneur.2018.00353
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bilateral Superior Branch Vestibular Neuropathy

Abstract: The rapid onset of a bilateral vestibular hypofunction (BVH) is often attributed to vestibular ototoxicity. However, without any prior exposure to ototoxins, the idiopathic form of BVH is most common. Although sequential bilateral vestibular neuritis (VN) is described as a cause of BVH, clinical evidence for simultaneous and acute onset bilateral VN is unknown. We describe a patient with an acute onset of severe gait ataxia and oscillopsia with features compatible with acute BVH putatively due to a bilateral V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
12
1
1
Order By: Relevance
“…In stark contrast, sacculus c-VEMP responses were normal, and utriculus o-VEMP responses were only weaker than normal on the right side. This report differs from a previous report of an acute BVL patient with only modest improvement in patient symptoms (22) in 3 aspects. Firstly, in our patient the loss involved all canal VOR responses and not just those served by the superior vestibular nerve (lateral and anterior canals).…”
Section: Introductioncontrasting
confidence: 99%
“…In stark contrast, sacculus c-VEMP responses were normal, and utriculus o-VEMP responses were only weaker than normal on the right side. This report differs from a previous report of an acute BVL patient with only modest improvement in patient symptoms (22) in 3 aspects. Firstly, in our patient the loss involved all canal VOR responses and not just those served by the superior vestibular nerve (lateral and anterior canals).…”
Section: Introductioncontrasting
confidence: 99%
“…(3), if at the same time it is called acute bilateral superior branch vestibular neuropathy (13). If hearing is also involved then the inner ear is assumed to be the site of lesion and the diagnosis becomes labyrinthitis (14).…”
Section: Discussionmentioning
confidence: 99%
“…If the patient also develops Benign Positional Vertigo (BPV) the term neurolabyrinthis ( 12 ) is used. If the other side is involved later, then this is called bilateral sequential vestibular neuritis ( 3 ), if at the same time it is called acute bilateral superior branch vestibular neuropathy ( 13 ). If hearing is also involved then the inner ear is assumed to be the site of lesion and the diagnosis becomes labyrinthitis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a reduction of VOR gain in bilateral lateral and anterior canals with posterior canal VOR gain being normal. 13 Isolated involvement of inferior vestibular nerve in vestibular neuronits is very rare. In a retrospective review by Kim et al, only 9 cases of 703 patients with vestibular neuronitis were found to have affected inferior vestibular nerve.…”
Section: Discussionmentioning
confidence: 99%